Short term outcome of pshycoeducational program on coping abilities of mother of children with cancer - Mohamad, Norsarwany; Hussin, Zabidi Azhar; Osman, Zubaidah Jamil; Blunden, Sarah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Objective: To evaluate a psycho-educational program (PeP) for parents ofchildren with cancer (PoCwC) in Malaysia. Methods: Seventy-nine parents were invited to be either in an intervention ( n = 41) or a control group ( n = 38 ). Baseline assessment took place upon agreement of participant. Shortterm effects were measured four weeks the intervention. Control parents received standard care. Intervention parents received in addition to standard care, 4 x 50 min sessions of information on childhood cancer and coping strategies. Result: Repeated measures of ANOVAs revealed increased knowledge about cancer ( p = 0.01 ) in the intervention parents compared with standard care. Intervention parents reported reduced anxiety and increased activities with children after the program; however, differences were not significant. · Conclusions: This PeP, the first of its kind in Malaysia, has significantly increased levels of knowledge among parents of seriously ill children which may point towards the potential for these services to increase coping in Malaysian PoCwC.